2021
DOI: 10.1097/nor.0000000000000741
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Delirium Nursing Model Initiatives to Determine the Incidence of Postoperative Delirium Among Elderly Orthopaedic Patients

Abstract: Delirium is a common neurocognitive disorder prevalent in hospitalized older adults. The development of delirium is associated with adverse health outcomes, including functional decline and mortality. This study aimed to investigate the incidence and risk factors of postoperative delirium in older adults (≥60 years) who underwent orthopaedic surgery. Elderly orthopaedic patients were recruited from a large urban hospital over 12 months. Patients were preoperatively screened for delirium and followed up at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, repeated disease attacks can easily affect the patient's work, life, and income, and increase the physical and mental burden of patients, which is not conducive to the stability of the disease and may lead to the occurrence of cognitive dysfunction in patients. Self-care is an important part of the treatment of chronic heart failure, but in clinical care, it is found that patients generally have a lack of disease awareness and poor self-management ability, which further affects disease control, aggravates the burden of self-cognition, and results in a vicious cycle [5][6]. The Information-Motivation-Behavioral Skills Model(IMB Model) can help patients achieve behavior change.…”
Section: Introductionmentioning
confidence: 99%
“…However, repeated disease attacks can easily affect the patient's work, life, and income, and increase the physical and mental burden of patients, which is not conducive to the stability of the disease and may lead to the occurrence of cognitive dysfunction in patients. Self-care is an important part of the treatment of chronic heart failure, but in clinical care, it is found that patients generally have a lack of disease awareness and poor self-management ability, which further affects disease control, aggravates the burden of self-cognition, and results in a vicious cycle [5][6]. The Information-Motivation-Behavioral Skills Model(IMB Model) can help patients achieve behavior change.…”
Section: Introductionmentioning
confidence: 99%